Payroll Administration Reform in Nigerian Civil Service: Assessing the Integrated Personnel and Payroll Information System - Folorunso , Olowu Olagunju; Iro, Uke Iro (Kashere Journal of Politics and International Relations, 2023)
The study examined payroll administration reform in Nigerian civil service with focus on the Integrated Personnel and Payroll Information System (IPPIS). The work was explorative research with qualitative method of sourcing data. Organizational process theory was adopted as the theoretical underpinning of the study to explain why some bureaucrats resist reform in civil service. The study found that the IPPIS software was introduced as part of payroll administration reform in the civil service and that the introduction of the IPPIS was mutually beneficial to both government and civil servants. The deployment of the software has helped the federal government to block the leakages associated to payroll fraud and on the other hand, it has resulted into seamless and timely payment of salaries to the civil servants despite the marginally perceived shortcomings of the payment platform. The study recommended among others that the gains should be sustained while the weaknesses should be worked upon to ensure efficiency and effectiveness of the platform, there is need by Office of Accountant General of the Federation and other related agencies manning IPPIS to urgently work on other six modules of the software in order to optimally utilize the platform beyond payroll module and that IPPIS payroll platform should be redesigned to accommodate institutional and organizational peculiarities.